Neodymium-doped yttrium aluminum garnet laser for minimally invasive management of limbal cysts in allergic conjunctivitis - Avadhesh Oli; Agrima Bhatia (Oman Journal of Ophthalmology, 2025)
Allergic conjunctivitis is a widely prevalent disease across the globe. Conjunctival congestion and papillae are the most common ocular manifestations. Limbal involvement in the form of limbitis is common but limbal cysts are very rare. We present a rare case of bilateral conjunctival inclusion cysts secondary to allergic conjunctivitis, successfully managed with neodymium-doped yttrium aluminum garnet (Nd: YAG) laser photodisruption. Unwilling for surgical excision, Nd: YAG laser was considered a minimally invasive, nonsurgical option to rupture the cysts. Over a follow-up period of seven months, all the cysts disappeared and the patient became symptom-free. This modality can be considered a minimally invasive alternative outpatient procedure to surgical excision with good outcomes, especially in cases with multiple small inclusion cysts as in our case.